Therapeutic Evaluation of Camel Milk-Derived Lactoferrin for in vivo Anti-Arthritic Efficacy - Dogra, Anchit; Mazumder, Avijit; Das, Saumya; Pandey, Pratibha; Lalitha Chaitanya, Motamarri Venkata Naga (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Arthritis is a prevalent chronic inflammatory condition that significantly impacts individual’s quality of life. Lactoferrin (Lf), a multifunctional glycoprotein found in CM, has shown promising anti-inflammatory and immunomodulatory properties. However, there is limited research on the anti-arthritic activity of Camel Milk (CM)-derived Lf. This study aims to evaluate the effectiveness of Lf isolated from CM in alleviating arthritis symptoms, providing valuable insights into its therapeutic potential for arthritis management. Objectives: The primary objective of this research is to assess the anti-arthritic activity of Lf isolated from CM. Materials and Methods: The anti-arthritic activity of Lf, administered was evaluated using two in vivo models. MSU induced arthritis model contained six groups containing six Wistar albino rats each. Negative control (Phosphate buffer saline), Positive control (monosodium urate crystals), Standard (indomethacin) and Test (CM, 5 mL/kg and 10 mL/kg, p.o and Lf 100 mg/kg, p.o). Collagen type-II induced arthritis model also contained six groups containing six Wistar albino rats each. Negative control (Phosphate buffer saline), Positive control (collagen type-II), Standard (ibuprofen) and Test (CM, 5 mL/kg and 10 mL/kg, p.o and Lf 100 mg/kg, p.o). Results: The data obtained from the a fore mentioned models demonstrated that Lf (100 mg/kg), in conjunction with CM administered at doses of 5 mL/kg and 10 mL/kg, exhibited anti-arthritic activity, resulting in a noticeable reduction in inflammation. Conclusion: This research study provides evidence supporting the effectiveness of Lf in alleviating arthritis symptoms by significantly reducing inflammation in the animal models tested.
Keywords: Lactoferrin; Camel milk; Monosodium urate crystals; Collagen type-II; Arthritis; Inflammation